DUSP10 upregulation is a poor prognosticator and promotes cell proliferation and migration in glioma - Zhou, Fang; Zeng, Lingfeng; Chen, Xi; Zhou, Fan; Zhang, Zhen; Yuan, Yixiao; Wang, Heping; Yao, Huayi; Tian, Jintao; Liu, Xujie; Zhao, Jinxi; Huang, Xiaobin; et al. (Frontiers in Oncology, 2023)
Dual-specificity phosphatase 10 (DUSP10) correlates with inflammation, cytokine secretion, cell proliferation, survival, and apoptosis. However, its role in glioma is unclear. Herein, we sought to examine the expression and the underlying carcinogenic mechanisms of DUSP10 action in glioma. DUSP10 expression in glioma was significantly higher than that in normal brain tissues. High DUSP10 expression indicated adverse clinical outcomes in glioma patients. Increased DUSP10 expression correlated significantly with clinical features in glioma. Univariate Cox analysis showed that high DUSP10 expression was a potential independent marker of poor prognosis in glioma. Furthermore, DUSP10 expression in glioma correlated negatively with its DNA methylation levels. DNA methylation level of DUSP10 also correlated negatively with poor prognosis in glioma. More importantly, DUSP10 expression correlated positively with the infiltration of B cells, CD4+ T cells, CD8+ T cells, neutrophils, macrophages, and dendritic cells in glioma. Gene set enrichment analysis (GSEA) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis confirmed that DUSP10 participated in signaling pathways involved in focal adhesion, TNF cascade, Th17 cell differentiation, and NF-kappa B cascade. Finally, we uncovered that DUSP10 was dramatically upregulated in glioblastoma (GBM) cells and that the knockdown of DUSP10 inhibited glioma cell proliferation and migration. Our findings suggested that DUSP10 may serve as a potential prognostic biomarker in glioma.